Pengaruh Tingkat Kesehatan Bank Terhadap Pertumbuhan Laba Perusahaan (Studi Pada Bank BUMN Yang Terdaftar Di BEI Periode 2008-2021) - Latifathul Rifda Nur Azizzah; Dessi Susanti (Jurnal Ecogen, 2023)
The purpose of this research is to investigate the impact of bank health level ratios on profit growth of state-owned banks listed on the IDX between 2008 and 2021. This study employs a quantitative approach to examine samples and populations through data analysis using panel data analysis and the statistical software Eviews version 12. Four State-Owned Commercial Banks used as research samples in this study. The results of this research is (1) the independent variables of banking health (NPL, LDR, GCG, ROA, and CAR) have no effect on the dependent variable of profit growth of state-owned bank companies for the 2008-2021 period, (2) the Non Performing Loan (NPL) variable has no effect on profit growth at state-owned banks for the 2008-2021 period, (3) the Loan to Deposit Ratio (LDR) variable, has no effect on profit growth at BUMN banks for the 2008-2021 period, (4) the Good Corporate Governance (GCG) variable has no effect on profit growth at BUMN banks for the 2008-2021 period, (5) the Return On Assets (ROA) variable has no effect on profit growth at BUMN banks for the 2008-2021 period, (6) the Capital Adequacy Ratio (CAR) variable has no effect on profit growth at BUMN banks for the 2008-2021 period.